Impossibility of the forced execution on real estate of Public Enterprises and for-profit corporations established by the Republic of Serbia - MItrović Igor (Trendovi u Poslovanju)
The paper deals with the issue of enforcement proceedings of real estate in public ownership in accordance with positive regulations of the Republic of Serbia, as well as the possibility of applying them in relation to the property of public enterprises and for-profit corporations established by the Republic of Serbia. Special emphasis is placed on legal regulation in terms of applying these regulations only to certain legal entities, more specifically, those which were not established by the Republic of Serbia. In which way, taking into account legal regulations, is the procedure of enforcement executed in relation to companies and entrepreneurships which were established by individuals; which objects and means of enforcement may be proposed by the enforcement creditor in the procedure of enforcement and in which way can the enforcement creditor, despite the fact that the Republic of Serbia appears as the founder of the Public Enterprise, may remain without settlement of a legally binding claim determined by an executive court decision. What are the advantages and disadvantages of the applicable Law on Enforcement and Security and how to regulate the legislation in this regard. For which reason, equal protection of rights before courts and other state bodies, holders of public authorities and autonomous provinces and local self-government units is not represented.